2014
DOI: 10.2215/cjn.04190413
|View full text |Cite|
|
Sign up to set email alerts
|

Provider and Care Characteristics Associated with Timing of Dialysis Initiation

Abstract: SummaryBackground and objectives There is a trend in the United States to maintenance dialysis initiation at higher levels of estimated GFR. This study aimed to determine whether provider characteristics and pre-ESRD nephrology care and vascular access are independently associated with higher estimated GFR at initiation.Design, setting, participants, & measurements This retrospective cohort study used US Renal Data System data for patients who initiated dialysis in 2006 (n=83,621) and American Medical Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
26
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
5
26
1
3
Order By: Relevance
“…Many of the specific patient characteristics associated with earlier dialysis initiation are similar to those previously observed in United States cohorts (2,7,9), and include female sex and presence of comorbidities. Prior studies have also suggested that patients with congestive heart failure initiate dialysis at higher eGFR values, likely to assist in the management of the patient's volume status (2,7).…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Many of the specific patient characteristics associated with earlier dialysis initiation are similar to those previously observed in United States cohorts (2,7,9), and include female sex and presence of comorbidities. Prior studies have also suggested that patients with congestive heart failure initiate dialysis at higher eGFR values, likely to assist in the management of the patient's volume status (2,7).…”
supporting
confidence: 59%
“…Many of the specific patient characteristics associated with earlier dialysis initiation are similar to those previously observed in United States cohorts (2,7,9), and include female sex and presence of comorbidities. Prior studies have also suggested that patients with congestive heart failure initiate dialysis at higher eGFR values, likely to assist in the management of the patient's volume status (2,7). It is likely that in Canada, similar to the United States, acceptance of older and sicker patients for dialysis therapy has contributed to the trend of rising eGFR at dialysis initiation because these patients typically are unable to tolerate uremia to the same degree as younger patients and they may have artificially higher eGFR estimates from their reduced muscle mass.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Those concerns must be weighed against the harm of placing fistulas in people who are never going to need them (55) and that may never mature (56). In addition, the presence of a mature fistula appears to be associated with a lower threshold to initiate hemodialysis (57). Patients can follow variable trajectories with CKD, which can help inform the transition point from observation to hemodialysis preparation (58).…”
Section: Beneficence and Nonmaleficence Need To Be Viewed Through Thementioning
confidence: 99%